Microstructure and Mechanical Properties of High-Entropy Alloy FeCoNiCr(X) Produced by Laser Directed Energy Deposition Process: Effect of Compositional Changes - Ekaterina Kovalenko; Igor Krasanov; Ekaterina Valdaytseva; Stanislav Stankevich; Olga Klimova-Korsmik; Marina Gushchina (Metals)
High-entropy alloys (HEAs) have shown promise as materials with improved mechanical properties compared to traditional materials. Achieving the desired mechanical properties depends on the alloy composition, both in terms of percentage and elements. Laser directed energy deposition technology allows for the production of products with various complex geometries and dimensions (L-DED). It has been found that HEA FeCoNiCrCu alloys can be divided into regions with high concentrations of Fe + Co + Cr and Cu elements. Dendrite growth directions of HEA FeCoNiCrCu are (111) and (200), and the average microhardness is around 240 HV. All samples have cracks vertically along the height. Fine-grained and dendrite structures were observed. Cu-element is mainly found in cracks. The HEA FeCoNiCrCu alloy was compared with another HEA FeCoCrMnNi, successfully obtained by the same L-DED technology. Comparing the two HEAs FeCoNiCrCu and FeCoCrMnNi obtained with the same deposition parameters can help determine the impact of one element on the phase composition, microstructure and mechanical properties of the high-entropy alloy. Replacing the element Mn with Cu in HEA FeCoNiCrMn led to a shift in the dendrite growth from one to two predominant directions and a decrease in the average microhardness by 20%.